Perbaikan Sistem Kerja Pada Industri Sepatu di CV. Civani Wanaraja-Garut - Fatimah, Dini Destiani Siti; Abdalah, Salman Nurdin; Haq, Faizal; Hidayatulloh, Endang Prayoga; Aprila, Dzikri; Rahman, Taupik; Nurzaman, Muhammad Zein; Amelia, Nadya; Oktapiani, Vini; Nurhaqiqi, Lisda; Aditia, Aditia; Alfarez, Rendi; Yusuf, Muhammad; Aldika, Alwin; Andriani, Ai Dini; Rahmadiani, Dina; Fahrezi, Filah; Mujahidin, Mujahidin; Ramadania, Sania Putri; Hanifah, Dinda; Efendi, Kurniawan; Kurniawan, Dede Rizki (Institut Teknologi Garut, 2023)
Standardization of work systems is necessary both for companies and for workers, standardization makes it easier for companies to make company plans and targets. For workers, standardization is a guide in making it easier for workers to do their work. This study aims to integrate the results of research conducted from 2022 and try it out, resulting in standardization of work systems in the shoe industry at CV. Civani which includes the specifications and physical form of the facilities used, work methods for each work station and the physical work environment that meets the job requirements. By standardizing the work system, it is hoped that workers will be more comfortable and safe in doing their jobs and help in achieving targets.